Drivers of Entrepreneurship and Post-entry Performance of Newborn Firms in Developing Countries - Quatraro, Francesco; Vivarelli, Marco (Oxford University Press on behalf of the World Bank, 2017)
The aim of this paper is to provide an updated survey of the “state of the art” in entrepreneurial studies with a particular focus on developing countries (DCs). In particular, the concept of “entrepreneurship” is critically discussed, followed by a discussion of the institutional, macroeconomic, and microeconomic conditions that affect the entry of new firms and the post-entry performance of newborn firms. The reviewed literature bears some policy implications for the support of the creation new firms, such as the targeting of policy measures to prospective entrepreneurs who possess high education levels, long previous job experience, and innovative skills. Specifically, for DCs, tailored subsidies and support should be coupled with framework and infrastructural policies that are able to improve the business environment such that new ventures can start and grow.